Effect of Different Levels of Moringa Leaves (Moringa oleifera) on Rumen Fermentation Pattern: An In Vitro Study - Keshri, Anchal; Dixit, Sonam; Tyagi, A.K. (Indian Journal of Animal Nutrition, 2022)
Present in vitro study was conducted to determine the potential of different levels of Moringa oleifera leaves powder as an additive to total mixed ration (TMRs) by assessing its effects on in vitro rumen fermentation characteristics. Concentrate mixture was replaced by different levels of Moringa leaves (ML) (0, 5, 10, 15, 25, 30, 40 and 50%) in a TMR (Roughage: Concentrate 60:40). They were then incubated for 24 h at 39°C in 100 ml calibrated glass syringes containing buffered rumen fluid. For every substrate, rumen fermentation parameters and methanogenesis were studied. It has been observed that ML improve the degradability of dry matter and organic matter, gas production, short-chain fatty acids production and decline the levels of methane emission compared to TMRs when fermented alone. The presence of ML in the total mixed ration exerted a positive associative effect on rumen fermentation parameters which resulted from an increase in net gas production, true degradability of dry matter, true degradability of organic matter and microbial biomass production with the simultaneous reduction in methanogenesis when compared TMRs alone. The addition of graded levels of ML resulted in increased volatile fatty acid production and ammonia nitrogen. This study revealed that the incorporation of ML improving the fermentation of TMRs and reducing methane emission. It was concluded that the ML can be incorporated in the animal ration without affecting animal performance.